A Modern way to teach Statistics, with an application - Abdelfattah, Ezz H. (European Journal of Applied Sciences, 2021)
The traditional way when teaching statistics is that Statistics has two main branches, namely Descriptive and Inferential statistics. The Descriptive statistics are brief descriptive coefficients that summarize a given data set, which can be either a representation of the entire or a sample of a population, While Inferential statistics are based on a random sample of data taken from a population to describe and make inferences about the population. The modern way we suggest for teaching statistics is to divide the Statistics into three branches. Namely Descriptive, Diagnostic and Predictive Statistics. In this paper, we will re-classify the inferential Statistics tests to Diagnostic Statistics tests and Predictive Statistics tests and give an applied example